Taxation and economic behaviour - Creedy, John (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2001)
This volume offers a number of broad introductory surveys in public economics and public finance. Divided clearly into two parts -measurement issues and taxation and economic behaviour - the collection consists of published refereed papers and several unpublished pieces.
Includes bibliographical references and index.
oif 05/08/16, ijb 19/03/2019
Loan
Keywords: Taxation; Income distribution; Welfare economics